PEDAGOGICAL CONDITIONS OF FOREIGN LANGUAGE TEACHING TO SCHOOLCHILDREN WITH MUSCULOSKELETAL DISORDERS (Modern education and development, 2025)
This article presents principles and practical ways of realization of pedagogical conditions as a factor of the pedagogical process.